Visualizing and disrupting liquid films for filmwise flow condensation in horizontal minichannels - Riley, Gennifer A.; Mendez, Carlos Espino; Egbo, Munonyedi; Hwang, Gisuk; Derby, Melanie M. (Frontiers in Thermal Engineering, 2022)
This paper investigates the effects of hemispherical mounds on filmwise condensation heat transfer in micro-channels. Also investigated were the impacts that spatial orientation of the three-sided condensation surface (i.e., gravitational effects) on steam condensation, where the cooled surfaces were either the lower surface (i.e., gravity pulls liquid towards the condensing surfaces) or upper surface (i.e., gravity pulls liquid away from the condensing surfaces). Two test coupons were used with 1.9-mm hydraulic diameters and either a plain copper surface or a copper surface modified with 2-mm diameter hemispherical mounds. Heat transfer coefficients, film visualization, and pressure drop measurements were recorded for both coupons in both orientations at mass fluxes of 50 kg/m2s and 125 kg/m2s. For all test conditions, the mounds were found to increase condensation heat transfer coefficients by at minimum 13% and at maximum 79%. When the test section was inverted (i.e., condensing surface on the top of flowing steam), minimal differences were found in mound performance, while the plain coupon reduces heat transfer coefficients by as much as 14%. Flow visualization suggests that the mounds enhanced heat transfer due to the disruption of the film as well as by reducing the thermal resistance of the film. Pressure drops followed parabolic behavior with quality, being higher in the mound coupon than the plain coupon. No significant pressure drop differences in the inverted orientation were observed.